Peran Pemuda Karo Dalam Membangun Komunitas Belajar Untuk Memenuhi Kebutuhan Belajar Anak Usia 7-12 Tahun Di Desa Samura - Ibnu Hajar; Ely Nina Kharina (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2022)
The problem in this research is how the role of Karo youth in building a learning community to be able to help meet the learning needs of children aged 7-12 years in Samudra Village. This study aims to describe the role of Karo youth in community development to help meet the learning needs of children aged 7-12 years in Samura Village.This type of research uses a descriptive approach with qualitative methods. The informants in this study were the Samura Village Head from the local government element, the FP3K Community (Forum Pemuda Peduli Pendidikan Karo), parents from the community element, and youth in Samura Village. The data collection techniques used were observation, interview and documentation techniques. The techniques used in data analysis are data collection, data reduction, data presentation, and drawing conclusions. Triangulation is carried out to explain the validity of the data by using source triangulation.The results showed that the role of youth in building a community to help meet the learning needs of children aged 7-12 years included: 1) The role in the planning stage, at this stage explaining the involvement of Karo youth in Samura Village in planning community development from the most basic stage. 2) The role in the implementation stage, at this stage the Karo youth of Samura Village are involved in implementing the programs in the FP3K (Forum Pemuda Peduli Pendidikan Karo) learning community in the Samura Village. 3) The role in the maintenance stage, at this stage the Karo youth are required to be able to keep the programs in the learning community running smoothly.Â Keywords: Role of Karo Youth, Learning Community, Learning Needs